More Left or Left No More? An In-depth Analysis of Western European Social Democratic Parties' Emphasis on Traditional Economic Left Goals (1944–2021) - Trastulli, Federico (Frontiers in Political Science, 2022)
The ideological evolution of Western European social democratic parties has received considerable scholarly attention over the decades. The most widespread view concerns the alleged programmatic moderation and convergence with the mainstream right of this party family. However, recent empirical investigations based on electoral manifestos come to different conclusions, highlighting an increase over time in Western European social democratic parties' emphasis on traditional economic left goals, especially in recent years. Hence, this article analyses the evolution of the social democratic programmatic outlook with regard to traditional economic left issues. It does so by relying on Manifesto Project (MARPOR) data about such formations in 369 general elections across 20 Western European countries between 1944 and 2021, employing different indicators of economic left emphasis and time to ensure the robustness of the findings. The analysis shows how, at the aggregate level, social democracy increases its emphasis on traditional economic left issues over time, with the effect driven entirely by the recent post-Great Recession years. However, once disaggregating the results, a more differentiated picture emerges, pointing towards potential causes of concern in terms of measurement validity within the MARPOR data. The article discusses the substantive and, especially, methodological implications of its findings in detail.